Determinants of Indonesian Muslim Students’ Intention to Online Infaq tn the Digital Philanthropy Era - Asnawi, Nur; Setyaningsih, Nina Dwi; Kamila, Talia Putri; Fanani, Muhammad Asnan (ZISWAF, 2026)
This study analyzes the behavioral intentions of Indonesian Muslim students to infaq using online platforms. The study uses quantitative methods and PLS-SEM to analyze data from 306 university students in major Indonesian cities. The results show that Past Behavior Frequency, Positive Anticipatory Emotions, Perceived Behavioral Control, Religious Beliefs, and Subjective Norms predict intention to donate online among Muslim students. Intention, past behavior frequency, perceived behavioral control, and religious beliefs also predict behavioral intention to donate online. Attitude toward online infaq and negative anticipatory emotions do not predict intention. The study offers theoretical and managerial insights for academics and managers of online donation platforms.